The relationship of university students’ childhood mental trauma with depression, anxiety and stress - Bahar, Aynur (The European Research Journal, 2023)
Objectives: The aim of this study is to examine the relationships between childhood mental trauma experiences, depression, anxiety and stress concepts. Methods: The research is a descriptive and relationship-seeking type of study. The study sample consisted of 192 students. Data were collected with the “Personal Information Form, Childhood Mental Trauma Scale and Depression Anxiety Stress Scale Short Form”. Results: The rate of students who stated that they were exposed to any trauma in their childhood is 74%. The majority of students reported physical (28.2%) and emotional abuse (33.1%). Those who were exposed to childhood traumas had high Depression Anxiety Stress Scale anxiety and depression subscale scores, and the difference between them was statistically significant. When the correlations between the scales are examined; There was a positive correlation between Depression Anxiety Stress Scale depression sub-dimension and Childhood Mental Trauma Scale total and physical abuse sub-dimensions, and a positive significant relationship between anxiety sub-dimensions and Childhood Mental Trauma Scale total, physical abuse, emotional abuse, and emotional neglect sub-dimensions. Conclusions: Childhood traumas are one of the important risk factors especially for depression and anxiety disorders. It can be recommended to take mental health measures to prevent the negative consequences of childhood traumas observed in adulthood, to provide psychosocial support to students and to include practices that will increase psychological resilience.